(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
A legal monster of the twentieth century: from technological warfare to its humanistic overcoming? ABSTRACT: The Author attempts to reconsider the dispute that has opened between Russie and Ukraine in the light not only of the evident flagrance of an abrupt, illegitimate ‘punitive expedition’ by Moscow towards a key territory for the control of the Black Sea, but also in the context of the great game of a power confrontation, never really concluded, between the two military blocs, despite the agreements on nuclear desarmament stipulated between Reagan and Gorbachev in the constituent phase of an unprecedented Russian Federation, after the passage from the start of a troubled liquidation of the Stalinism to the announced overcoming of the blockade policy. A context, against which NATO’s failure to comply with the mutual commitment of the two parties to the complete cessation of mutual hostile conduct, prior to perestroika, seems full and flagrant. The essay recognizes in the event the clear failure of an apparent opening of trust towards the post-communist counterpart, internal to the substantial maintenance of an armed peace with a world to be kept for a long time in a sort of quarantine on the margins of “Western civilisation”, for an indefinite period and under the strict control of an internationalized military apparatus of exorbitant dimensions. A dead-end road, destined to produce even partial moments of exploitation of the repressive functions of the UN, rather than supporting its fundamental role of “saving future generations from the scourge of war”. To such a logic the A. tries to escape, in an attempt to bring the cooperation relationships laboriously woven into the fabric of international relation back to a framework of substantial good faith, from human subjects whose trust and honor always seem due, until rigorously proven otherwise; in the belief that progressive success can only come to these relations by restoring a framework that favours the basic ethical choices on the UN statute, as an indispensable background for constructive settling of potential situations of conflict of interest, which arise between member states in the course of their peaceful cooperation towards an orderly sharing of the planet’s resources. SOMMARIO: 1. Preambolo - 2. La guerra ‘giusta’ in Occidente. Tra Tarda Antichità e Medioevo del diritto - 3. (segue) Evoluzione del problema nell’età dell’imperialismo - 4. Interrogativi sulla resistenza non violenta come verità più profonda sull’uomo - 5. (segue) Fra realismo politico e profezia del Regno (Mt. V, 38-48) - 6. Centralità della Croce: l’imitazione del processo a Gesù negli “Acta martyrum” - 7. (segue) Fede e ragione. Il doppio registro dell’economia salvifica - 8. Quadro sintetico dei residui ostacoli sulla via di un mondo diverso e solidale - 9. (segue) Sull’incompatibilità tra deterrenza e trattativa. L’ammonimento cinese - 10. Etica confuciana, diritto romano, diritto canonico. La Cina, oggi - 11. Dal ‘maschio alfa’ al giudice. Agli albori del divieto di vendetta privata - 12. (segue) Su un’Autorità addetta al controllo dell’aggressività interstatale - 13. Verso una nuova guerra ‘giusta’? Dubbi di fondo sulla nozione di aggressione - 14. Una NATO senza legge verso un gioco, di cui nessuno è responsabile? - 15 (segue) Sottrarre la neutralizzazione all’autonomia degli stati? - 16. È già irricevibile una tardiva ’actio finium regundorum’ sotto garanzia ONU? - 17. Quali altre vie per la missione di una ‘Russia eterna’, nella fraternità dei popoli? - 18 (segue) Quasi una conclusione.